Greenhouse Gas Emission Reduction through Electricity Generation from Solar Photovoltaic Systems: A Study in Dhaka (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
Though best provided with electricity, Dhaka, the capital city of Bangladesh, often experiences power outages while lacking at least 500 MW of electrical power. Given a massive shortage of electricity both in Dhaka and the country and the use of fossil fuels in power generation, the present study examines the potential of rooftop solar photovoltaics (SPVs) for electricity generation in the Dhaka Metropolitan Area (DMA) and the consequent greenhouse gas (GHG) emission reduction. It has been found that the roof area of DMA is 62 km2. Considering 50% of this area (31 km2), the application of SPVs can generate 9,454 GWh of electricity yearly or 25.8 GWh per day. Such generation can reduce GHG emissions by 4.3 MtCO2e/year, which is 26.7% of the NDC target from the power sector. The results of this study support the wide-scale application of rooftop SPVs throughout DMA.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 12(1), 2023, P 1-8